NILAI TAMBAH PENGOLAHAN IKAN SALAI PATIN (Kasus di Desa Penyasawan Kecamatan Kampar, Kampar) - M. Ramli; Intan Putri Anggarini (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
Analysis of value-added processing smoked catfish (Patin) aims to see how mucheconomic value added processing received a catfish processing businesses seekinga fresh fish preparations. Catfish of 500 kg of fresh fish when processed into150kg of smoked fish with a selling price of Rp5,5000.00 per kg, while the price ofraw materials Rp 1,3000.00 per kg. After the analysis of its known economicvalue of Rp 2,926.00 per kg(17.73%) with a profit of Rp1,726.00 per kg(58.99%).Margin value of output at a price of raw materials amounting to Rp 3,500.00.Key words: Value-added, catfish processing